Enhancing photoelectrochemical performance and stability of Ti-doped hematite photoanode via pentanuclear Co-based MOF modification - Dong, Guofa; Xie, Fengyan; Kou, Fangxia; Chen, Tingting; Xiao, Caihong; Du, Shaowu; Liang, Jiaqi; Lou, Chenfang; Zhuang, Jiandong (Frontiers in Chemistry, 2024)
Modifying photoanodes with metal-organic frameworks (MOFs) as oxygen evolution reaction (OER) cocatalysts has emerged as a promising approach to enhance the efficiency of photoelectrochemical (PEC) water oxidation. However, designing OER-active MOFs with both high photo- and electrochemical stability remains a challenge, limiting the advancement of this research. Herein, we present a facile method to fabricate a MOF-modified photoanode by directly loading a pentanuclear Co-based MOF (Co-MOF) onto the surface of a Ti-doped hematite photoanode (Ti:Fe2O3). The resulting Co-MOF/Ti:Fe2O3 modified photoanode exhibits an enhanced photocurrent density of 1.80 mA∙cm−2 at 1.23 V, surpassing those of the Ti:Fe2O3 (1.53 mA∙cm−2) and bare Fe2O3 (0.59 mA∙cm−2) counterparts. Additionally, significant enhancements in charge injection and separation efficiencies, applied bias photon-to-current efficiency (ABPE), incident photon to current conversion efficiency (IPCE), and donor density (Nd) were observed. Notably, a minimal photocurrent decay of only 5% over 10 h demonstrates the extraordinary stability of the Co-MOF/Ti:Fe2O3 photoanode. This work highlights the efficacy of polynuclear Co-based MOFs as OER cocatalysts in designing efficient and stable photoanodes for PEC water splitting applications.